ADAPTATION AND PROGRESS THROUGH CHANGE MANAGEMENT - MEHEDINTU, Gabriela; MUNTEANU, Ana (Annals of Spiru Haret University. Economic Series, 2016)
The technological progress, digitization and the explosion of information significantly change how individuals, the business environment, and society act, develop and add value. New, interdisciplinary approaches, constantly adapted and sustainable both at the micro and the macro levels are required. Within a company, change management is a systematic element of the strategic business process and involves the early identification of the opportunity of the employees’ development, courage, commitment and flexibility; under no circumstances should it be seen as a risk and instability factor, as it may be considered in the early stages. The example presented in this article proves that the openness to change and continuous improvement develops advantages, optimizes processes and sustains long-term progress.